Tales from Facebook - Miller, Daniel, 1954- (Cambridge, UK : Polity Press, 2011)
Facebook is used by nearly 500 million people throughout the world. Once the preserve of youth, the largest increase in usage today is amongst the older sections of the population. This book examines how Facebook transforms the lives of particular individuals, but it also presents a general theory of Facebook as culture and considers the likely consequences of social networking in the future.
Includes bibliographical references.
Keywords: Facebook (Electronic resource); Online social networks; Information technology -- Social aspects